LITERASI DI ERA DIGITAL DENGAN POBASCO (POJOK BACA SCAN ONLINE) - Syahda Nur Fadilah; Oktaviani Melly Wicecari; Wahyu Hidayat; Audi Pramudita Anggilia; Nabila Syifa Ramadhani; Dewi Trynasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology demands strengthening student literacy from elementary school, not only in reading and writing skills but also in digital literacy. However, low student reading interest and suboptimal use of devices for learning activities remain issues in elementary schools. This study aims to describe how the POBASCO (Online Scan Reading Corner) digital literacy program is implemented and its impact on students' reading interest and digital literacy at SDN Ngale 01, Madiun Regency. This study used a qualitative descriptive approach and collected data through observation, interviews, and documentation. The research subjects included fourth to sixth grade students, teachers, and the community surrounding the school. The results indicate that the use of QR codes with POBASCO can increase students' interest in reading digital books, direct their use of devices for educational activities, and help them learn more independently. This program also helps strengthen the school's literacy culture by involving teachers and the community, aligning with the implementation of the School Literacy Movement. Thus, POBASCO can be a contextual and relevant alternative for implementing digital literacy innovations in elementary schools.